Gastric carcinoid in the absence of atrophic body gastritis and with low Ki67 index: a clinical challenge. (April 2014) - Lahner, Edith; Pilozzi, Emanuela; Esposito, Gianluca; Galli, Gloria; Annibale, Bruno
Abstract Background. Gastric carcinoids (GCs) represent 23% of all digestive neuroendocrine tumors (NETs). They can be distinguished into three types: type I (in the presence of atrophic body gastritis, ABG), type II (in the presence of Zollinger-Ellison/multiple endocrine neoplasia type I syndrome), type III (sporadic carcinoids, without any background pathology). Aim. To describe a case of undetermined type of GCs in an Italian referral center for NETs and its prevalence among GCs during a 6-year period. Results. In a case series of 16 GCs seen at our unit between 2007 and 2012, 14 (83.3%) patients had type I carcinoid and 1 patient (6.2%) had type III carcinoid. One patient did not accomplish to the actual classification criteria. This patient had a well-differentiated carcinoid with low Ki67, but multiple gastric biopsies performed at 3-year follow-up gastroscopies excluded the presence of ABG. The patient had fundic cystic polyps, suggesting long-term use of proton pump inhibitors, possibly associated with GCs. Conclusions. This case shows that a GC may occur in the absence of ABG and with low Ki67 index, making classification according to actual criteria difficult. Further studies are needed to better understand the occurrence of this particular type of GCs.